Near-infrared light-activated membrane fusion for cancer cell therapeutic applications. Issue 21 (21st May 2020) - Huang, Fujian; Duan, Ruilin; Zhou, Zhixin; Vázquez-González, Margarita; Xia, Fan; Willner, Itamar
Abstract : A NIR light activatable membrane fusion method was developed for cancer cell therapeutic applications. Abstract : The spatiotemporal stimulation of liposome–liposome or liposome–membrane fusion processes attracts growing interest as a means to mimic cell–cell interactions in nature and for using these processes for biomedical applications. We report the use of o -nitrobenzyl phosphate functionalized-cholesterol tethered nucleic acid-modified liposomes as functional photoresponsive units for inducing, by NIR-irradiation, spatiotemporal liposome–liposome or liposome–membrane fusion processes. The liposomes are loaded with upconversion nanoparticles (UCNPs) and their NIR irradiation ( λ = 980 nm) yields luminescence at λ = 365 nm, providing a localized light-source to deprotect the o -nitrobenzyl phosphate groups and resulting in the fragmentation of the nucleic acid structures. In one system, the NIR-triggered fusion of two liposomes, L1 and L2, is exemplified. Liposome L1 is loaded with UCNPs and Tb 3+ ions, and the liposome boundary is functionalized with a cholesterol-tethered, o -nitrobenzyl phosphate caged hairpin nucleic acid structure. Liposome L2 is loaded with 2, 6-pyridinedicarboxylic acid, DPA, and its boundary is modified with a cholesterol-tethered nucleic acid, complementary to a part of the caged hairpin, associated with L1 . NIR-irradiation of the L1 /L2 mixture resulted in the photocleavage of the hairpin structure, associated with L1, and the resulting fragmented nucleic acid associated with L1 hybridized with the nucleic acid linked to L2, leading to the fusion of the two liposomes. The fusion process was followed by dynamic light scattering, and by monitoring the fluorescence of the Tb 3+ –DPA complex generated upon the fusion of the liposomes and their exchange of contents (fusion efficiency 30%). In a second system, the fusion of the liposomes L1, loaded with UCNPs and doxorubicin (DOX), with HeLa cancer cells functionalized with nucleic acid tethers, complementary to the hairpin units associated with the boundary of L1, and linked to the MUC-1 receptor sites associated with the HeLa cells, through a MUC-1 aptamer unit is exemplified. The effect of DOX-loaded L1 /HeLa cell fusion on the cytotoxicity towards HeLa cells is addressed. The NIR UCNP-stimulated cleavage of the o -nitrobenzyl phosphate caged hairpin units associated with L1 leads to the fragmentation of the hairpin units and the resulting nucleic acid tethers hybridize with the nucleic acid-modified HeLa cells, resulting in the liposome–HeLa cell fusion and the release of DOX into the HeLa cells. Selective spatiotemporal cytotoxicity towards HeLa cells is demonstrated ( ca. 40% cell killing within two days). The study presents a comprehensive stepwise set of experiments directed towards the development of NIR-driven liposome–liposome or liposome–membrane fusion processes.